An ordered one-step colorimetric sensor for the selective determination of catechol based on the polyacrylic acid-coated cerium oxide with laccase-like activity. (14th November 2022) - Jiang, Xiaoyan; Wang, Min; Hou, Li; Lin, Tianran
Abstract : A sensitive colorimetric sensor was constructed for an ordered and one-step determination of catechol based on PAA-CeO2 with a significant laccase-like activity. Abstract : A one-step colorimetric sensing platform had been constructed for catechol determination based on polyacrylic acid-coated cerium oxide (PAA-CeO2 ) with a significant laccase-like activity. Compared with the traditional nanozyme-based colorimetric determination methods for catechol, the PAA-CeO2 nanozyme with laccase-like activity did not require biotoxic and poor stability H2 O2 in this method. PAA-CeO2 could directly catalyze the oxidation of catechol to o -quinone in the presence of dissolved O2, and the oxidation product was coupled with 4-aminoantipyrine (4-AAP) to form a pink product at the maximum absorption of 512 nm (OD512 ). By utilizing the relationship between the concentration of catechol and the OD512 intensity to achieve sensitivity quantitative analysis and visual determination of catechol in an ordered and one-step reaction, which provided a dynamic range from 0.5 to 50 μmol L −1 within a low detection limit of 0.121 μmol L −1 . In addition, this colorimetric sensing platform based on PAA-CeO2 had satisfactory repeatability and stability, which could be used for the catalytic degradation of other phenolic compounds in the environment to ensure public health and environmental safety.